Filmonomics economists discuss the silver screen - Palma, André de 1952-; LeRuth, Luc (Routledge, Taylor & Francis Group, 2025)
"What could movies as diverse as The Last Samurai, Cléo from 5 to 7, or Dr. Strangelove have in common? Filmonomics has a simple yet intriguing answer: economics as the main driving force of the plot or as the main motivation of the characters' actions. This book analyses how movie makers use economic and financial motives in their plots or to build their characters. Have they done it in line with economic theory? Or are they proposing a new angle, a new perspective, that economists should take note of? The authors here do not discuss wages in the film industry or the economics of movies. What interests them is the economic motivations underpinning the behaviour of fictional characters in their favorite films. They argue that credible movie characters can behave in irrational ways, and movie makers occasionally introduce new ideas that economists should take note of. A unique contribution, this book will be of interest to readers eager to discover what economists have to say about films and film directors. It will be indispensable for students and researchers of economics, media studies, film studies, and cultural studies"--
Keywords: Economics in motion pictures; Motion pictures / Plots, themes, etc; Économie politique au cinéma; Cinéma / Intrigues, thèmes, etc; Aufsatzsammlung